Risk Factors and Indirect Costs in Chronic Kidney Failure Patients with Hemodialysis in dr. Drajat Prawiranegara Hospital Serang - Hasna Dewi; Prih Sarnianto; Nurita Andayani (Jurnal Biologi Tropis, 2023)
Increased prevalence of chronic kidney failure from time to time will increase, causing significant economic pressure, both for patients and their families and other stakeholders. This study aims to determine the main factors and several advanced CRF risk factors and indirect costs incurred from a household perspective in CRF patients with hemodialysis at Dr. Drajat Prawiranegara Serang Regional Hospital. This type of research is Case Control Study. Data analysis is carried out using three stages, namely univariate, bivariate, and multivariate. The results of bivariate statistical analysis show that of the 21 CRF risk factors there are 15 factors that are statistically significant with P-value 00 0.005. These factors consist of sociodemography, biophysiology, lifestyle. The results of multivariate analysis, the most dominant causing chronic kidney failure (GGK) is kidney stone disease with a risk of 9.6 times compared to without a history of this disease. Then, NSAID consumption history is 7.8 times, herbal consumption. Indirect costs from the household perspective are seen from the transportation costs of each arrival, the cost of eating during hemodialysis therapy and the purchase of multivitamins or medicines that are not borne by insurance/BPJS, other costs such as lodging and personal care. The total minimum cost for each arrival is Rp. 47,250 Maximum Rp. 1,970,000. The monthly fee is 8 times the minimum total expenditure, which is Rp. 96,000 and maximum spending Rp. 9,120,000.